3D-printed carbon fiber/polyamide-based flexible honeycomb structural absorber for multifunctional broadband microwave absorption. (15th November 2021) - Gong, Ping; Hao, Liang; Li, Yan; Li, Zheng; Xiong, Wei
Abstract: The growing demand of wearable device and the irreplaceable roles in stealth technique have boosted the exploration of high-performance flexible microwave absorbers. Herein, a novel flexible honeycomb structural absorber (FHSA) of carbon fiber (CF)/polyamide (PA)/carbonyl iron (CIP) composite was successfully fabricated via selective laser sintering (SLS) 3D-printing. The CFs arrangement and unit-structure were rationally controlled during the SLS 3D printing process for acquiring enhanced microwave absorption (MA) property, especially for the high bending angles. Therefore, under the high bending angle of 150°, the minimum reflection loss of the designed FHSA can reach −47 dB at 16.2 GHz with a broadband absorption of 13.2 GHz, covering the whole C2, X, and Ku bands, which breaks the traditional restraints that the flexible absorbers can only have the high MA property in tiling or minor bending status. In addition, the FHSA also showed the advantages of highly flexible deformation, self-recovery and no-crease damage in repeated bending, which could largely improve the environment applicability. This work provides a controllable strategy for the design of flexible microwave absorber, showing potential applications in wearable functional devices and military stealth protection. Graphical abstract: Image 1 Highlights: Carbon fiber (CF)/polyamide (PA)-based flexible absorber is prepared by 3D printing. CF/PA-based flexible microwave absorber can improve environment applicability. Enhanced microwave absorption property is achieved by controlling CFs arrangement. Under the bending angle of 150°, the broad effective bandwidth can reach 13.2 GHz. Multimaterials, structures and fabrication method achieve effective collaboration.